-5 -2(x+3) + 7x
= -5 -2x -6 + 7x
= -11 -2x + 7x
= 5x - 11
2006-11-07 00:18:17
·
answer #1
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
0⤋
-5 -2 (x+3) + 7x distribute the 2
-5 -2x + (-6) + 7x
then combine the like terms
x's: -2x+7x= 5x
negative numbers: -5 + (-6)= -11
answer
-11+5x
2006-11-06 13:14:40
·
answer #2
·
answered by trish the dish 3
·
0⤊
0⤋
-5 - 2(x+3) + 7x
-5 + -2(x+3) + 7x
-5 + -2x + -6 +7x
-11 + 5x
The answer: -11 + 5x
2006-11-06 12:47:25
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
-5 -2(x+3) + 7x -> -5 -2x -6 +7x -> 5x - 11
2006-11-06 12:46:03
·
answer #4
·
answered by Richard S 6
·
0⤊
0⤋
initiate via utilising the distributive components to get rid of parenthesis: 3(x-4) = 3x - 12, so 5 + 3 ( x - 4 ) - x = 5 + 3x - 12 - x no combine like words: 3x - x is 2x and 5 - 12 is -7, so 5 + 3x - 12 - x = 2x - 7 ...answer D)
2016-10-21 09:39:04
·
answer #5
·
answered by ? 4
·
0⤊
0⤋
-5 [-2(x+3)] + 7x
-5 (-2x-6)+ 7x
10x+30+7x
17x+30
2006-11-06 12:50:56
·
answer #6
·
answered by Latina129 2
·
0⤊
0⤋
-5-2x-6+7x
5x-11
5x = 11
x=11/5
x=2 1/5
2006-11-06 12:43:55
·
answer #7
·
answered by EAA Duro 3
·
0⤊
0⤋
-5-2x-6+7x
combine like terms
5x-11
2006-11-06 12:42:42
·
answer #8
·
answered by kiyomidog 2
·
0⤊
0⤋
The answer is 5x-11. You should really do your homework by yourslef though. Getting the answers from here will not help you pass the test.
2006-11-06 12:41:23
·
answer #9
·
answered by Joe 2
·
0⤊
0⤋
-5-2x-6+7x
5x-11
2006-11-06 12:42:46
·
answer #10
·
answered by ceni40 3
·
0⤊
0⤋